Atmospheric dryness thresholds of grassland productivity decline in China. (15th July 2023) - He, Panxing; Han, Zhiming; He, Mingzhu; Meng, Xiaoyu; Ma, Xiaoliang; Liu, Huixia; Dong, Tong; Shi, Mingjie; Sun, Zongjiu
Abstract: Atmospheric dryness events are bound to have a broad and profound impact on the functions and structures of grassland ecosystems. Current research has confirmed that atmospheric dryness is a key moisture constraint that inhibits grassland productivity, yet the risk threshold for atmospheric dryness to initiate ecosystem productivity loss has not been explored. Based on this, we used four terrestrial ecosystem models to simulate gross primary productivity (GPP) data, analyzed the role of vapor pressure deficit (VPD) in regulating interannual variability in Chinese grasslands by focusing on the dependence structure of VPD and GPP, and then constructed a bivariate linkage function to calculate the conditional probability of ecosystem GPP loss under atmospheric dryness, and further analyzed the risk threshold of ecosystem GPP loss triggered by atmospheric dryness. The main results are as follows: we found that (1) the observed and modeled VPD of Chinese grasslands increases rapidly in both historical and future periods. VPD has a strongly negative regulation on ecosystem GPP, and atmospheric dryness is an important moisture constraint that causes deficit and even death to ecosystem GPP. (2) The probability of the enhanced atmospheric dryness that induced GPP decline in Chinese grasslands in the future period increases significantly. (3) When the VPD is higher than 40.07 and 27.65 percentile of the past and future time series, respectively, the risk threshold of slight ecosystem GPP loss can be easily initiated by atmospheric dryness. (4) When the VPD is higher than 82.57 and 65.09 percentile, respectively, the threshold of moderate ecosystem GPP loss can be exceeded by the benchmark probability. (5) The risk threshold of severe ecosystem GPP loss is not initiated by atmospheric dryness in the historical period, and the threshold of severe ecosystem GPP loss can be initiated when the future VPD is higher than 91.92 percentile. In total, a slight atmospheric dryness event is required to initiate a slight ecosystem GPP loss threshold, and a stronger atmospheric dryness event is required to initiate a severe ecosystem GPP loss. Our study enhances the understandings of past and future atmospheric dryness on grassland ecosystems, and strongly suggests that more attention be invested in improving next-generation models of vegetation dynamics processes with respect to the response of mechanisms of ecosystem to atmospheric dryness. Highlights: VPD regulates ecosystem GPP by inhibiting plant growth. The probability of future atmospheric dryness causing GPP decline is higher than ever. Future slight atmospheric dryness could initiate severe GPP loss thresholds.